PENGGUNAAN APLIKASI YOUTUBE SEBAGAI MEDIA DAKWAH DI ERA PANDEMI COVID-19 - Prihantoro N P; M. Fais Noor M; Hisny Fajrussalam; I Makna A’raaf K; Sifa Larasati (UIN Sunan Kalijaga, 2021)
The existence of the Covid-19 pandemic is the background for holding this research, in which health protocols prohibit and limit activities that gather large numbers of people. This also has an impact on religious activities such as da'wah which require alternative solutions, because previously it was carried out face-to-face and gathered. The alternative offered in this study is through the social media platform Youtube. The purpose of this study is to analyze whether the Youtube platform is effectively used for preaching and to find out the methods applied in da'wah through the Youtube platform. This study uses a qualitative method, where data is collected from reliable sources such as explanations of the Qur'an and Hadith. The results of this study indicate that da'wah through the Youtube platform in the era of the Covid-19 pandemic has several advantages compared to conventional da'wah. Youtube has many advantages, such as being widely accessed by various groups in terms of sharing video content. Youtube and da'wah also have a relationship with segmentation that both target audiences. In this case, it is hoped that ustaz, scholars, and preachers can use Youtube media by using the available features. This also needs to be followed by good and correct da'wah methods in accordance with Islamic teachings.